Rozczarowana ponowoczesność a status utopii/dystopiiwe współczesnym imaginariumi w praktykach kulturowych - Bielska, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2023)
The topic of analysis is the status of utopia in postmodern social space (taking into account it’s normative, structural and cultural components). One of the elements of the postmodern structure of knowledge and ideas is deconstruction of the modern imaginaries related to the potential availability of the means and tools that would enable creation of the society more and more predictable, safe and free of crisis (political, economic, social). Postmodernity, therefore, express disappointment with the modern model of imaginaries and characteristic for it components like: trust to scientific knowledge and scientists as well as conviction of the stability and predictability of the event are replaced by the irony.
Keywords: postmodernity; utopia; imaginaries